Effects of copper levels on goat carcass traits and meat quality - López Puga, Jocelyn Cyan; Rico Costilla, Daniela Saraí; Sobrevilla Hernández, Gustavo; Moreno Degollado, Gustavo; Kawas Garza, Jorge R.; Méndez Zamora, Gerardo (2021)
The objective of the current study was to evaluate high levels of dietary copper (Cu) on goat carcass traits and meat quality. Thirty-six French Alpine goats (18.43 ± 2.35 kg) were randomly assigned to 6 treatments (basal diet with Cu levels at 0, 10, 20, 40, 80, and 160 ppm) with 6 replications each. The experiment was carried out for 102 d. Plasma Cu and enzymes, and slaughter variables were not different (P > 0.05) between Cu levels. Cu in the goat diets was significant (P < 0.05) for meat lightness (L*) and yellowness (b*); L* values were higher (P <0.05) at 20 ppm and lower (P < 0.05) at 10 and 80 ppm; b* was highest (P < 0.05) for the 160 ppm level and lowest (P < 0.05) for 40 ppm. Meat adhesiveness presented differences (P < 0.05) between Cu levels; the 10 ppm group showed the highest value (P < 0.05) and 0 ppm the lowest value (P < 0.05). Meat juiciness for 10 ppm was higher (P < 0.05) than meat for the 80 ppm group. Linear regression demonstrated that b* and springiness were dependent (β1 ∕= 0; P ≤ 0.05) on Cu levels in the diet. In conclusion, high Cu levels are recommended in the goat diet to enhance meat quality without affecting slaughter variables.